PRESERVING TRADITIONAL CULTURE OF KONDA-KONDI THROUGH MOBILE GAME APPLICATIONS - Din, Suhaili; Shahrull Ramadzan, Qhairul Aizat (Journal of Computing Technologies and Creative Content, 2019)
Traditional games are now disremembered so it is time to bring back the memories of our childhood and make it alive throughout the next generation. The focus of this research is to develop a sense of awareness and cultivate them in our people sentiments. Konda-kondi will be turned into an interesting app to attract the children rather than having them playing some worthless games. By using the mobile application, the developer wants to introduce the supreme of traditional game of konda-kondi. Adobe Animate is use to build a mobile interactive game that user can interact with and enjoy the forgotten game of konda-kondi.